Desenvolvimento de marcadores microssatélites para Ololygon centralis (Anura: Hylidae) por sequenciamento de segunda geração com baixa cobertura - Castro, Andrezza Arantes (2018)
The ease access to Next Generation Sequence methodologies has improved the development of several projects, once it makes possible the de novo assembly of DNA sequences, creating a great amount of data and giving access to unknown genomes of different organisms. The anuran species Ololygon centralis belong to Hylidae family. It is considered as endemic of Cerrado Biome and little is known about its genomics. The aim of this work was to realize a draft of the genome of O. centralis in order to identify, to characterize, to quantify repetitive elements and to predict possible genes. Also, we aimed to develop microsatellite markers for the species. The genome draft assembled in 13989 scaffolds, which correspond to 4926069 bp with N50 = 336. The repetitive elements found in the O. centralis genome (1795 transposons, 957, microsatellite, one satellite DNA and 25 small nuclear RNAs) comprised 531337 bp. Between the retrotransposons, the LINE element (49,83%) was the most abundant, followed by LTR (48,66%) and SINE (1,56%). It was possible to identify coding genes for the 5S, 18S and 28S subunits of ribosomes. Also, 18 types of coding regions for tRNA and 26 putative genes were found in the O. centralis genome. From the microsatellite regions, it was possible to design 87 pairs of primers for the flanking sites. There were found 47 regions composed of tetranucleotides, 39 dinucleotides and on trinucleotide on the microsatellite sites. From them, 31 pairs of primers were selected for amplification and 18 showed good results. The annealing temperatures varied from 50° e 60° C. Seven markers showed polymorphism. From them, only 5 markers (PCE05, OCE11, PCE20, OCE21, OCE26) were used to characterize the genotype of 30 individuals. The medium number of alleles was 10, the allelic amplitude varied from 148 bp (OCE20) to 318 bp (OCE21). The Expected Heterozygosity was 0,7 and the observed was 0,5. The probability of parentage exclusion (Q) was 0,993 and the probability of combined identity (I) was 1,13x10-6. The global value of the fixation index (FST) was significant and equal to 0,2 (p<0.05). The data obtained from the NGS Illumina platform represent one important step for the knowledge of genomics of this species and of the anuran in general.